I will attempt to prove that \(\pi = -\pi \). In which of these steps did I make a flaw in my logic?

**Step 1:** Using a famous theorem, \[e^{i\pi } = -1 . \]
**Step 2:** Reciprocate both sides of the equation: \[e^{-i\pi} = \dfrac{1}{-1} = -1 . \]
**Step 3:** Equating both equations in the above two steps gives
\[ \large e^{i \pi} = e^{-i \pi} . \]
**Step 4:** Since the bases are the same,
\[ i \pi = -i \pi . \]
**Step 5:** Canceling the imaginary number yields
\[ \pi = -\pi .\]

×

Problem Loading...

Note Loading...

Set Loading...